2015
DOI: 10.1371/journal.pone.0129144
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in NFKB1 and NFKBIA and Susceptibility to Coronary Artery Disease in a Chinese Uygur Population

Abstract: ObjectivesCoronary artery disease (CAD) is the most common chronic inflammatory disease worldwide. NF-κB, a central regulator of inflammation, is involved in various inflammatory diseases. The aim of this study was to investigate the association between NFKB1 and NFKBIA polymorphisms and the susceptibility to CAD and their impact on plasma levels of IL-6 in a Chinese Uygur population.MethodsWe genotyped NFKB1-94ins/del ATTG (rs28362491) and NFKBIA3’ UTR A/G (rs696) using TaqMan SNP genotyping assays in 960 Uyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
3
17
0
Order By: Relevance
“…Inflammation represents an important feature in the process of atherosclerosis, which can form, destabilize, and rupture atherosclerotic plaques, finally causing CHD [ 29 ]. Over the years, researchers have found some inflammatory factors related to the pathogenesis and prognosis of CHD, such as CLOCK SNP rs4580704 [ 30 ], ICAM-1 SNP rs281432 [ 31 ], and NFKB1 SNP rs28362491 [ 32 ]. Some of these inflammation-related genes were expected to be drug targets for the control and treatment of CHD.…”
Section: Resultsmentioning
confidence: 99%
“…Inflammation represents an important feature in the process of atherosclerosis, which can form, destabilize, and rupture atherosclerotic plaques, finally causing CHD [ 29 ]. Over the years, researchers have found some inflammatory factors related to the pathogenesis and prognosis of CHD, such as CLOCK SNP rs4580704 [ 30 ], ICAM-1 SNP rs281432 [ 31 ], and NFKB1 SNP rs28362491 [ 32 ]. Some of these inflammation-related genes were expected to be drug targets for the control and treatment of CHD.…”
Section: Resultsmentioning
confidence: 99%
“…All participants were selected from the Cardiovascular Risk Survey (CRS) study, aged from 35 to 88 years and recruited between 2007 and 2010. Full details of the CRS study have been published elsewhere [ 16 ]. The study was approved by the Ethics Committee of the First Affiliated Hospital of Xinjiang Medical University and was conducted in accordance with the standards of the Declaration of Helsinki (Ethics Approval Number:20080724).…”
Section: Methodsmentioning
confidence: 99%
“…This result was consistent with our previous studies. Our previous studies reported that this variation was correlated with CAD in Chinese Han and Uygur populations 15,36 . Therefore, together with these above-mentioned studies, these findings clearly indicated the NFKB1 gene rs28362491 variation was more likely to be an independent risk factor for susceptibility of MI.…”
Section: Discussionmentioning
confidence: 81%
“…NFKB1 gene rs28362491 encodes p50/p105 submits of NF-κB family and locates at chromosome 4q24. A four base ATTG insertion/deletion (ins/del) variation located in −94 loci of NFKB1 promoter has been reported, which encodes three genotypes: wild-type homozygous insertion (II genotype), variant homozygous deletion (DD genotype) and heterozygous (ID genotype) 15 . Studies have shown that individuals who carried NFKB1 gene rs28362491 D allele or DD genotype were more susceptible to inflammatory diseases such as inflammatory bowel disease 16 , ulcerative colitis 17,18 and atherosclerotic cardiovascular diseases including coronary artery disease (CAD) [19][20][21] in different populations.…”
mentioning
confidence: 99%